Еffect of structure and mineralogical features of silica raw material on phase changes during heating; Refractories and Industrial Ceramics; Vol. 50, № 1 - Vakalova T. V. Tatyana Viktorovna (2009, 2009)
It is established that the sequence and intensity of polymorphic transformations of silica raw material on heating in the range 1000 – 1200°C are explained by features of its chemical and phase composition. Differences in structure and phase changes determine the different degree of activity for this raw material during synthesis of silicate compounds.